Sustainable tourism in protected areas - Strunjak, Elizabeta (Crisis Management Days, 2024)
Throughout history, various geological changes took place, after which natural beauties were created. Unfortunately, due to human activity, much of the uniqueness and richness of nature has diminished over time. Part of the priceless natural wealth was thus lost, and it was realized that the irrational use of natural resources can cause irreversible changes and thus irreparable damage to man. We are becoming aware that nature conservation and tourism must not be rivals, but our primary goal must be global awareness of nature conservation. Due to their exceptional beauty and uniqueness, certain areas of nature must be protected and preserved. However, if we want to protect them and at the same time enable long-term management of tourism in these areas, it is necessary to implement sustainable tourism that will fully consider its current and future economic, social and environmental impact and meet the needs of visitors, industry, the environment and host communities. The concept of sustainable development is emerging as a response to the extremely rapid growth of the world's population. Growing disparities in socioeconomic development and rapid environmental degradation led to sustainable development at the beginning of the 1990s. It is defined as a form of development that meets the needs of present generations without endangering the equal opportunities of future generations. We can reduce the negative impacts of tourism on natural beauty by developing sustainable and socially responsible tourism. For the quality implementation of sustainable tourism in protected areas, it is necessary to strategically plan and implement various activities and a visitor management model. In the paper, this model is shown on the example of the Dubravica Special Botanical Reserve, which was almost destroyed at the beginning of this millennium, but managed to be preserved thanks to the efforts and work of the Public Institute and the local community. Therefore, it is necessary to work on preservation in the future as this protected area has become part of the identity and symbol of the destination. The paper used methods of description and interpretation whose data were found in scientific literature. However, qualitative research, i.e. a semi-structured interview with an expert in the field of nature protection, was used to investigate the specific example. In short, for the successful development of sustainable tourism in protected areas, it is necessary to set threshold values for acceptable changes, to determine the instruments of nature protection and sustainable development, as well as to determine conservation areas and regimes for conservation goals. In addition, it is necessary to establish interactive strategic networks, a visitor management model, but also to analyze possible problems and monitor activities and management efficiency.